Decomposition of Wood by Termites in Different Types of Land Use - Sri Heriza; Damayanti Buchori; Idham Sakti Harahap; Nina Maryana (Universitas Gadjah Mada, 2022)
Decomposition is an important process in nature, as it can break down organic matter into smaller particles and nutrients. Nutrients are returned to the environment and can be reused by other organisms. One important organism that plays a role in the decomposition process is termites because termites are able to decompose organic matter such as wood in all habitats. Different termite habitats can be seen in terms of different types of land use. Some types of land use, such as natural forests, secondary forests, palm oil plantations, and settlements, can be used as a test site for wood decomposition by termites. All types of land use can be found in Dharmasraya Regency, West Sumatra Province. The purpose of this study was to study the decomposition of wood by termites in several different types of land use. Four types of land use are selected from habitats with the least disturbed conditions to the extent of high habitat disturbances, namely natural forests, secondary forests, palm oil plantations, and settlements. The study was conducted in Dharmasraya Regency, West Sumatra Province. The research method uses pine wood bait (Pinus merkusii), measuring 1.9 cm x 1.9 cm x 25 cm. The wooden bait is winded for seven days, and the wood bait is weighed to gain its initial weight and measured moisture content. Furthermore, wood bait that has been installed is observed and re-weighed to gain final weight and measured water content. The results showed that deforestation in Dharmasraya, West Sumatra had an effect on reducing wood decomposition by termites. Five (5) termite species were found in wood bait, including Pericapritermes sp.1, Microtermes sp.1, Schedorhinotermes sp.1, Macrotermes gilvus, and Coptotermes curvignathus.